Three constituents with biological activity from Coccoloba uvifera seeds - Moreno Morales, Shailili; Crescente Vallejo, Oscar; Henríquez Guzmán, William; Liendo Polanco, Gustavo; Herrera Mata, Hernando (Ciencia)
“Uvero de playa” (Coccoloba uvifera Jacq.) seeds were extracted with methanol and the antibacterial, antifungal, toxic and phototoxic activities were determined together with their phytochemical analysis. The extract was active against Salmonella typhimurium and Staphylococcus aureus, showing the presence of flavonoids, saponins, polyphenols and tannins. The partition with EtOAcof the MeOH extract gave a brown precipitate that inhibited the growth of Escherichia coli and Pseudomonas aeruginosa, and showed antifungal activity against Candida albicans, Fusarium oxysporum and F. decencellulare. This solid was fractionated by means of vacuum columns (low pressure columns) chromatographies, molecular exclusion and bidimensional paper chromatographies obtaining a tannic compound, an organic acid and a benzopyran from the bioactive fractions. These compounds were identified by means of IR, GC/MS and NMR (1H and 13C) as: gallic acid, hexenedioic acid and 1,3,4,6,7,8”“hexahydro-4,6,6,8,8,8- hexamethylcyclopenta- 2- benzopyran.